EFFECTIVENESS OF GLOBALIZATION AND HUMAN CAPITAL ON MARKET & NET INCOME INEQUALITY IN BRICS COUNTRIES: A PANEL DATA ANALYSIS - Walayat, Khaula; Qamar, Dr. Mahmood Khalid; Iqbal, Dr. Zahid Iqbal (Journal of Arts & Social Sciences, 2022)
This study scrutinizes the impact of defacto and dejure GLOB (KOF GLOB index 2018) on Income inequality on economically emerging countries; BRICS countries. The defacto GLOB indicates the estimate of GLOB including variables representing activities and flows; de jure estimate includes variables which show policies representing enable flows and activities. Our analysis separates the impact of globalization on net and market income inequalities. Pretax/transfer and the post-tax/transfer GINI indices were employed as the measures of income inequality. This analysis used balanced panel for BRICS countries for the period 1990-2015. Economic globalization both defacto and dejure showed positive sign that depicts a significant relationship with dependent variable. It explains that defacto political has positive sign and dejure political globalization decreases inequality while economic globalizations in both divisions have positive sign and significant impact on inequality. Interestingly, defacto social globalization has positive sign but dejure social has positive sign. Moreover, the purchasing power parity and age dependency both have negative sign and significant influence on inequality. These conclusions point out that social and political globalization may be a hindering factor for governance in these countries.